Palladium-Catalyzed C(sp3)-H Arylation of Benzo[b]thiophen-3(2H)-one 1,1-Dioxide - Hailong Liu; Wenjing Li; Haiyan Fu; Hua Chen; Ruixiang Li; Yu Li (Journal of Chemistry)
A new concise synthesis route of 2-phenylbenzo[b]thiophen-3(2H)-one 1,1-dioxide from benzo[b]thiophen-3(2H)-one 1,1-dioxide was developed using palladium-catalyzed C(sp3)-H arylation. Compared with the traditional route, this protocol can effectively save many steps and combine with the current research hotspot, C(sp3)-H activation. Moreover, this catalytic system is easy to operate and a good yield can be achieved.